Optimal switching and condition-based maintenance of cold standby systems subject to competitive failure and imperfect switchover - He, Yugang; Zhang, Xiaohong; Wu, Xinyu; Zhang, Jianfei; Shi, Guannan; Qin, Yankai (The Journal of the Operational Research Society, 2024)
Cold standby redundant structures can improve system reliability and availability but are subjected to internal degradation and external shocks during operation. Thus, the switching process in a standby system is prone to failures. This study investigates the optimal switching and condition-based maintenance (CBM) decision of a two-unit cold standby system subject to mutually dependent competitive failure processes with an imperfect switchover. First, periodic switching and offline CBM policies under imperfect switchover are proposed; second, the reliability models of competitive failure-between soft failure caused by system degradation subject to nonfatal shock and hard failure caused by fatal shock-are established. An iterative model of the system state probability distribution is subsequently derived by analysing the characteristics of state transitions in alternate use and maintenance of the active and standby units. An analytical decision model is also established to minimise the average cost rate in a finite horizon to obtain the optimal switching period and maintenance threshold. Finally, a case study of a coal mine main ventilator system validates the proposed model.